2015
DOI: 10.1080/09168451.2015.1065170
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative properties of ginsenoside Ro against UV-B-induced oxidative stress in human dermal fibroblasts

Abstract: Ginsenoside Ro (Ro), an oleanolic acid-type ginsenoside, exhibited suppressive activities on reactive oxygen species (ROS) and matrix metalloproteinase-2 (MMP-2) elevation in UV-B-irradiated fibroblasts. Ro could overcome the reduction of the total glutathione (GSH) contents in UV-B-irradiated fibroblasts. Ro could not interfere with cell viabilities in UV-B-irradiated fibroblasts. Collectively, Ro possesses a potential skin anti-photoaging property against UV-B radiation in fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…2). Previous researches on ginsenoside Ro mostly involved in the anti-inflammatory 28, 29 , thrombosis prevention 30, 31 and anti-oxidation 32 . The most eye-catching newly discovery of ginsenoside Ro is its autophagy inhibition activity, which beyond several other ginsenosides extraceted form Panax ginseng 33 .…”
Section: Discussionmentioning
confidence: 99%
“…2). Previous researches on ginsenoside Ro mostly involved in the anti-inflammatory 28, 29 , thrombosis prevention 30, 31 and anti-oxidation 32 . The most eye-catching newly discovery of ginsenoside Ro is its autophagy inhibition activity, which beyond several other ginsenosides extraceted form Panax ginseng 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Activated NF‐κB eventually binds to κB elements in the promoter region of target genes and initiates the transcriptional process of numerous genes . Recent investigations have demonstrated that the NF‐κB pathway is suppressed by a large number of ginsenosides, including Rg1, Rh2, Rb1, Compound K (CK), Rg3, Rb3, Rd, Pseudoginsenoside‐F11 (PF11), Re, Rh1, Rf, 20( S )‐protopanaxatriol, and Ro (Fig. ).…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 93%
“…NF‐κB‐mediated activation of downstream genes is proposed to be closely correlated with inflammation‐associated cancer . Through inactivating the NF‐κB pathway, ginsenosides exhibit an inhibitory effect on human cancer in the following three aspects: (1) cancer metastasis was shown to be blocked by three different ginsenosides.…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%
“…Re, which is a PPT-type ginsenoside, was demonstrated to preserve skin barrier functionality, via enhancing CE formation, and potentiating filaggrin and caspase-14 activity in skin cells under physiological conditions (43). Ro, an oleanolic acid-type ginsenoside, also exhibited anti-photoaging potential by counteracting the UVB-induced decrease in fibroblast GSH contents (44). These previous findings suggested that ginsenosides may exert beneficial actions on human skin; however, the mechanisms underlying their effects may vary depending on the type of ginsenoside and their stereospecificity.…”
Section: Discussionmentioning
confidence: 99%